Упростить (a-6)^2-a(a+6)= 6a(a+b)(a-b)= -3b(c+b)(b-c)= (a-5)(a+5)+25= (7+a)(a-7)-(a^2-70)= (b-4)(b+4)-b(b-2)= x(x+8)+(x+2)(2-x)=

  • 03-02-2007 05:06
  • Просмотры: 11
Ответы ( 1 )
МАШКА ПОТОЦЬКАЯ
+1
03-02-2007 16:36

1)(a-6)^2-a(a+6)=a-12a+36-a-6a=-18a+36 2)6a(a+b)(a-b)=6a(a-b)=6a-6ab 3)-3b(c+b)(b-c)=-3b(b-c)=-3b+3bc 4)(a-5)(a+5)+25=a-25+25=a 5)(7+a)(a-7)-(a^2-70)=a^2-49-a^2+70=21 6)(b-4)(b+4)-b(b-2)=b-16-b+2b=2b-16 7)x(x+8)+(x+2)(2-x)=x+8x+4-x=8x+4 Пусть новый учебный год только удачу тебе принесет!

Похожие вопросы